Effects of Dlx2 overexpression on the genes associated with the maxillary process in the early mouse embryo - Sun, Jian; Zhang, Jianfei; Bian, Qian; Wang, Xudong (Frontiers in Genetics, 2023)
The transcription factor Dlx2 plays an important role in craniomaxillofacial development. Overexpression or null mutations of Dlx2 can lead to craniomaxillofacial malformation in mice. However, the transcriptional regulatory effects of Dlx2 during craniomaxillofacial development remain to be elucidated. Using a mouse model that stably overexpresses Dlx2 in neural crest cells, we comprehensively characterized the effects of Dlx2 overexpression on the early development of maxillary processes in mice by conducting bulk RNA-Seq, scRNA-Seq and CUT&Tag analyses. Bulk RNA-Seq results showed that the overexpression of Dlx2 resulted in substantial transcriptome changes in E10.5 maxillary prominences, with genes involved in RNA metabolism and neuronal development most significantly affected. The scRNA-Seq analysis suggests that overexpression of Dlx2 did not change the differentiation trajectory of mesenchymal cells during this development process. Rather, it restricted cell proliferation and caused precocious differentiation, which may contribute to the defects in craniomaxillofacial development. Moreover, the CUT&Tag analysis using DLX2 antibody revealed enrichment of MNT and Runx2 motifs at the putative DLX2 binding sites, suggesting they may play critical roles in mediating the transcriptional regulatory effects of Dlx2. Together, these results provide important insights for understanding the transcriptional regulatory network of Dlx2 during craniofacial development.